2014
DOI: 10.3329/jbau.v12i1.21413
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of quality status and detection of adulterants in selected commercial pickles and chutneys based on consumer attitude and laboratory analysis

Abstract: Quality of selected commercial pickles and chutneys were evaluated by conducting a baseline survey on the consumer attitude towards the products and analyzing the selected products for adulterants and performing sensory evaluation. The pickle and chutney samples were analyzed in selected accredited laboratories for the physicochemical parameters such as fluid portion percent by mass of the net mass, acidity as citric acid (% mg/gm), sodium benzoate (mg/Kg), arsenic (mg/Kg), Lead (mg/Kg), copper (mg/Kg), zinc (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
3
4
0
Order By: Relevance
“…Higher fluid content also has the effect of speeding up rancidity and causing the formation of off flavors. Similar findings were reported by Rahman et al (2014), when they studied quality standards of commercial pickles and chutneys. Rahman et al (2019) also reported, with an increase in storage time, fish pickles' moisture content dropped when they were kept stored in refrigeration and frozen temperature.…”
Section: Moisture Content Of Chutney and Picklessupporting
confidence: 87%
See 3 more Smart Citations
“…Higher fluid content also has the effect of speeding up rancidity and causing the formation of off flavors. Similar findings were reported by Rahman et al (2014), when they studied quality standards of commercial pickles and chutneys. Rahman et al (2019) also reported, with an increase in storage time, fish pickles' moisture content dropped when they were kept stored in refrigeration and frozen temperature.…”
Section: Moisture Content Of Chutney and Picklessupporting
confidence: 87%
“…Sodium benzoate was determined following the method described by Rahman et al (2014). The calculation was conducted using following formula, Concentration of Benzoic acid (mg/kg) = Here, N, V, V 1 and W denote normality of the standard sodium hydroxide solution, volume of standard sodium hydroxide solution, volume of filtrate taken and mass in g of the material respectively.…”
Section: Determination Of Sodium Benzoatementioning
confidence: 99%
See 2 more Smart Citations
“…The quality of chutney depends on the cooking duration which is long enough below the boiling point to avoid fermentation. The high sugar and acid content of chutneys are the basis of preservation and flavour development is achieved by addition of different spices (Rahman et al 2014). In Uttarakhand state of India, chutneys are made from locally available plant parts viz.…”
Section: Types and Varieties Of Traditional Picklesmentioning
confidence: 99%